2007
DOI: 10.2136/vzj2006.0109
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Migration in a Radially Divergent Flow Field: Longitudinal Dispersivity and Anionic Tracer Retardation

Abstract: Hydrodynamic dispersion, the combined effects of chemical diffusion and differences in solute path length and flow velocity, is an important factor controlling contaminant migration in the subsurface environment. However, few comprehensive three‐dimensional datasets exist for critically evaluating the impact of travel distance and site heterogeneity on solute dispersion, and the conservative nature of several commonly used groundwater tracers is still in question. Therefore, we conducted a series of field‐scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
(130 reference statements)
2
14
0
1
Order By: Relevance
“…As might be expected for a system displaying amphoteric surface charge, minimal colloid generation occurred when the pH (∼5.0–5.5) and solution composition were similar to the low ionic strength groundwater typical of the water‐table aquifer on the SRS. Additionally, the duration of our study was insufficient to alter the groundwater chemistry in all but the closest monitoring wells, as confirmed by subsequent groundwater tracer studies (Seaman et al, 2007). Therefore, colloid mobilization here likely resulted from a combination of formation disturbance during well installation and the altered hydraulic gradient associated with injection and groundwater sampling.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As might be expected for a system displaying amphoteric surface charge, minimal colloid generation occurred when the pH (∼5.0–5.5) and solution composition were similar to the low ionic strength groundwater typical of the water‐table aquifer on the SRS. Additionally, the duration of our study was insufficient to alter the groundwater chemistry in all but the closest monitoring wells, as confirmed by subsequent groundwater tracer studies (Seaman et al, 2007). Therefore, colloid mobilization here likely resulted from a combination of formation disturbance during well installation and the altered hydraulic gradient associated with injection and groundwater sampling.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, our objectives were (i) to evaluate the impact of injection rate on colloid generation as a function of depth within the formation and distance from the injection well and (ii) to evaluate the impact of colloid mobilization on water quality and formation permeability in the vicinity of the injection well. We used information gained during the initial test to plan and design subsequent long‐term injection experiments to evaluate the impact of solution chemistry on colloid mobilization, as well as for several extensive groundwater tracer experiments (Seaman et al, 2007).…”
mentioning
confidence: 99%
“… 3 H 2 O is more conservative than Br − in anion‐sorbing sediments (Seaman et al 1995; Korom 2000). Br − adsorption is nonlinear (i.e., concentration‐ dependent), resulting in greater tailing (i.e., dispersion) than apparent for a “conservative” tracer (Seaman et al 1995; Seaman et al 1996; Korom 2000; Seaman et al 2007). Korom (2000), in a column study using an undisturbed sand with Br − concentrations from <0.1 to 700 mg/L, found the sorption was best fit by a second‐order polynomial; however, a Freundlich isotherm also described the adsorption within a 95% confidence interval on the regression. Br − sorption increases with increasing concentrations (Korom, 2000), as suggested by Figure 1B with pH < PZC.…”
Section: Anions In Groundwatermentioning
confidence: 99%
“…The variances of the natural logarithms of the hydraulic conductivity fields were varied over an order of magnitude and two operationally defined parameters were considered: the amount of Br − injected and the lowest tracer concentration value used in the dispersivity computations as a result of analytical quantification limits for the tracer or because of measureable background concentrations of the tracer (Korom and Dodak 2009). Using two FBA tracers, Br − , and 3 H 2 O in a series of field‐scale forced‐gradient tracer tests, Seaman et al (2007) found that the assumption of conservative behavior for the anionic tracers generally yielded larger longitudinal dispersivity values than did the experiments using 3 H 2 O. They also concluded that advection‐dispersion models reasonably “appeared” to describe the non‐conservative anion tracer transport without accounting for anion sorption, indicating that geochemical interactions with the aquifer sediment may be interpreted incorrectly in terms of physical transport processes (i.e., flow velocity, dispersivity, multiple flow domains, etc.…”
Section: Anions In Groundwatermentioning
confidence: 99%
“…Diese können durch die Überlagerung mehrerer aDM-Kurven simuliert werden (z. b. Seaman et al 2007). Für jede einzelne Kurve müssen die Werte für t 0 und D bestimmt werden.…”
Section: Verwendete Modelleunclassified